FAKTOR, KRITERIA DAN ASPEK: TINJAUAN KEWARGANEGARAAN - Azizi, Khodadad (Fakultas Dakwah dan Komunikasi Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
Citizenship Education can be stated as an effort in the educational process because it has broad aspects related to political or governmental issues in the development of citizens. In strengthening good planning in citizenship, of course, it must be supported by various things, both in terms of criteria, aspects and also the factors that influence it. From the curriculum side, the curriculum must also be active in supporting the achievement of civic competence, which means that the curriculum can meet changes in line with the times, science and technology. In addition, there needs to be a good approach in the implementation process. The approach can be done in a scientific way. Various aspects that exist in the values ​​of Pancasila must be embodied with norms and ethics. These norms are used as guidelines for good behavior in society. Moral is also an academic and non-academic education, which means what good behavior is then applied to life in society. In citizenship education, there are two necessary factors. Namely, contextual factors (internal) and structural factors (external). Contextual factors related to material concepts. In terms of structural factors which are related to institutions or institutions where the educational process is carried out. Apart from that, it is also to find out the extent to which the quality and quantity of implementing citizenship in a country can be seen from the attainment of the criteria for citizenship education itself. The criteria can be seen in terms of the minimum criteria and also the maximum criteria in achieving citizenship education in a country.